Galectins: a potential pharmacological target - V. A. Serebryakova; O. E. Vaizova; E. L. Golovina; V. V. Kochubey (Бюллетень сибирской медицины, 2024)
Aim. To consider the use of galectin-1 and galectin-3 inhibitors as potential pharmacological targets in antitumor and antifibrotic therapy.The lecture includes the analysis of experimental research and review articles presented in the PubMed database. A brief description of the structure of galectins is given. Their generally accepted classification and features of the structure of the carbohydrate recognition domain in galectin-1 and galectin-3 are presented. The main part of the lecture describes the results of research on the development of carbohydrate-based (β-galactoside derivatives or analogues) and non-carbohydrate-based (peptide-based, carboxamide derivatives) inhibitors capable of interacting with galectin-1 and galectin-3.The results of experiments performed on animal models and tumor cell cultures demonstrate that the antitumor effect of galectin antagonists is realized through the suppression of proliferation and metastasis, activation of tumor cell apoptosis, and modulation of the antitumor immune response. Antagonists of galectin-1 and galectin-3 potentiate the effect of antitumor drugs and have an antifibrotic effect. Some of the compounds discussed in the lecture are undergoing clinical trials. The data presented in the lecture open up opportunities for the development and synthesis of new molecules of potential galectin-1 and 3 inhibitors.